On The Interpretation of Instrumental Variables in the Presence of Specification Errors: A Causal Comment - Burkhard Raunig (Econometrics, 2017)
Swamy et al. (2015) argue that valid instruments cannot exist when a structural model is misspecified. This note shows that this is not true in general. In simple examples valid instruments can exist and can help to estimate parameters of interest.